1978
DOI: 10.1530/jrf.0.0540363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive immunization against oestrogens on the onset of parturition in the ewe

Abstract: Summary. Six ewes were treated twice daily with intravenous injections of antiserum to oestrogens and 3 ewes received normal sheep serum from Day 140 of gestation until parturition. All 9 ewes experienced normal parturitions and produced healthy active lambs after similar gestation lengths. Progesterone and prostaglandin F concentrations in maternal jugular venous plasma were similar in the immunized and control ewes, but total unconjugated oestrogen concentrations were significantly higher in the immunized ew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, Ricketts, Sheldrick, Lindsay & Flint (1980) were unable to confirm this finding. Rawlings, Pant & Ward (1978) found that ewes passively immunized against oestrogens were able to deliver normally, but this study does not conclusively exclude the participation of oestrogens in normal ovine parturition because, as the authors them¬ selves point out, a locally operating mechanism involving oestrogen would not have been excluded.…”
Section: Plasma Progesterone Titresmentioning
confidence: 65%
“…However, Ricketts, Sheldrick, Lindsay & Flint (1980) were unable to confirm this finding. Rawlings, Pant & Ward (1978) found that ewes passively immunized against oestrogens were able to deliver normally, but this study does not conclusively exclude the participation of oestrogens in normal ovine parturition because, as the authors them¬ selves point out, a locally operating mechanism involving oestrogen would not have been excluded.…”
Section: Plasma Progesterone Titresmentioning
confidence: 65%